RKIP and TBK1 form a positive feedback loop to promote type I interferon production in innate immunity. (17th October 2016) - Gu, Meidi; Liu, Zhiyong; Lai, Rongrong; Liu, Si; Lin, Wenlong; Ouyang, Chuan; Ye, Sheng; Huang, He; Wang, Xiaojian
Abstract: TANK‐binding kinase 1 (TBK1) activation is a central event in type I interferon production in anti‐virus innate immunity. However, the regulatory mechanism underlying TBK1 activation remains unclear. Here we report that Raf kinase inhibitory protein (RKIP) is essential for TBK1 activation and type I interferon production triggered by viral infection. Upon viral infection, RKIP is phosphorylated at serine 109 (S109) by TBK1. Phosphorylation of RKIP enhances its interaction with TBK1 and in turn promotes TBK1 autophosphorylation. Mutation of RKIP S109 to alanine abrogates the interaction between RKIP and TBK1, and the anti‐viral function of RKIP. RKIP deficiency inhibits intracellular double‐stranded RNA‐ or DNA‐induced type I interferon production. Consistently, RKIP deficiency renders the mice more susceptible to vesicular stomatitis virus (VSV) and herpes simplex virus (HSV) infections. This study reveals a previously unrecognized positive feedback loop between RKIP and TBK1 that is essential for type I interferon production in anti‐viral innate immunity. Synopsis: TBK1 plays a central role in type I interferon production in innate immunity. Here we show that the TBK1–RKIP loop is important for TBK1 activation during anti‐viral innate immunity. Upon viral infection, TBK1 phosphorylates RKIP, which enhances its interaction with TBK1 and in turn promotes TBK1 autophosphorylation. RKIP is critical for anti‐viral innate immunity both in vitro and in vivo . RKIP is essential for autophosphorylation of TBK1 upon virus infection. TBK1 phosphorylates RKIP at serine 109. S109 phosphorylation is essential for RKIP to promote TBK1 autophosphorylation. Abstract : A positive feedback loop involving TBK1 and its substrate RKIP (Raf kinase inhibitory protein) is essential for interferon responses in virus‐infected mice.